COMMUNICATION STRATEGIES TO OVERCOME LINGUISTIC BARRIERS: A SNAPSHOT OF INDONESIAN POSTGRADUATE STUDENTS AS A SECOND LANGUAGE LEARNER LIVING IN TARGET LANGUAGE COMMUNITY - Yuliandri (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2019)
Being able to communicate effectively in English on both social and academic setting, is one of the biggest challenge faced by International students learning in English speaking countries like New Zealand. This challenge is inevitably relevant to students from Indonesia, a country where English is not a second language. Extra effort is required since these International students must be able to learn and produce the language simultaneously in a very immediate context, shifting from EFL to ESL context. To be able to shift from these two different learning contexts, specific strategies are needed. The use of communication strategies is purposed to assist language learners in a target language community in delivering and receiving messages in spoken communication. This research is aimed to: a) identify types of communication strategy used by Indonesian Adult Postgraduate students; b) investigate how these communication strategies are learned and applied. The data is collected qualitatively through semi-structured interviews. The result of this study reveals that, the two respondents in general are using the same communication strategies: compensatory strategy in form of circumlocution; in addition, avoidance strategy is also applied as a last resort. Furthermore, this research also highlights learning strategies developed/learned by the respondents to upgrade their communication competence.